Karthago, Tunesien. Datengesteuerte Modellierung des Romanisierungsprozesses in Nordafrika. Forschungsergebnisse des Jahres 2020 - Schweigart, Fleur (e-Forschungsberichte des DAI, 2021)
As part of the Math+ Emerging Field 5 »Concept of change in historical processes« (EF5-2), the project »Data-driven Modeling of the Romanization Process in Northern Africa«, which started in 2019, attaches on the interface between mathematics and archaeology. The aim of the project is to develop data-driven and network-based approaches for computational modeling of social and cultural changes with archaeological data to reconstruct and visualize cultural changes as a result of new historical developments. For this purpose, the Romanization in Northern Africa – with focus on the region of Tunisia – is evaluated in an interdisciplinary cooperation between the Zuse-Institut, Berlin (ZIB) and the German Archaeological Institute (DAI).